2007
DOI: 10.1080/08860220701460160
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis C in Patients Receiving Hemodialysis

Abstract: Hepatitis C virus (HCV) infection is frequent in patients with end-stage renal disease treated by chronic dialysis, with a prevalence varying from 10-65% according to the geographical data. The prevalence is significantly associated with the duration of dialysis and the number of transfused blood products [1,2] and has dramatically declined with efficient blood screening. [3] We studied patients with acute HCV infection in a dialysis unit. The diagnosis was based on both anti-HCV detection and HCV-RNA detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Six studies were excluded because they did not fulfill the inclusion criteria [Potthoff et al, 2005;Carbognin et al, 2006;Caro et al, 2007;Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008] or contained duplicate reports of the same patients [Kokoglu et al, 2006]. Three studies concerned pegylated IFN for acute hepatitis C [Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008]. The remaining 16 studies [Mukherjee et al, 2003;Annichiarico and Siciliano, 2004;Rivera et al, 2005;Teta et al, 2005;Covic et al, 2006;Russo et al, 2006;Sporea et al, 2006;Amarapurkar et al, 2007;Casanovas-Taltavull et al, 2007;Chan et al, 2007;Espinosa et al, 2007;Akhan et al, 2008;Ayaz et al, 2008;Liu et al, 2008;Sikole et al, 2008;UcMak et al, 2008] representing a total of 254 unique patients, were included in the metaanalysis.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Six studies were excluded because they did not fulfill the inclusion criteria [Potthoff et al, 2005;Carbognin et al, 2006;Caro et al, 2007;Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008] or contained duplicate reports of the same patients [Kokoglu et al, 2006]. Three studies concerned pegylated IFN for acute hepatitis C [Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008]. The remaining 16 studies [Mukherjee et al, 2003;Annichiarico and Siciliano, 2004;Rivera et al, 2005;Teta et al, 2005;Covic et al, 2006;Russo et al, 2006;Sporea et al, 2006;Amarapurkar et al, 2007;Casanovas-Taltavull et al, 2007;Chan et al, 2007;Espinosa et al, 2007;Akhan et al, 2008;Ayaz et al, 2008;Liu et al, 2008;Sikole et al, 2008;UcMak et al, 2008] representing a total of 254 unique patients, were included in the metaanalysis.…”
Section: Literature Reviewmentioning
confidence: 97%
“…All candidate studies were written in English. Six studies were excluded because they did not fulfill the inclusion criteria [Potthoff et al, 2005;Carbognin et al, 2006;Caro et al, 2007;Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008] or contained duplicate reports of the same patients [Kokoglu et al, 2006]. Three studies concerned pegylated IFN for acute hepatitis C [Engel et al, 2007;Griveas et al, 2007;Lederer et al, 2008].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Little is known regarding the treatment of acute hepatitis C in this population, and only a small number of observational studies have been published [61][62][63]. In general, these studies demonstrated that IFN alfa or PEG-IFN alfa therapy is effective; each produced SVR rates of 57-86% and was well tolerated [61,62,64,65], but further studies are required.…”
Section: Treatment Of Acute Hepatitis C Among Hemodialysis Patientsmentioning
confidence: 98%
“…Recent recommendations to monitor ALT in HD population may facilitate detection of cases of acute HCV [122][123][124][125][126][127][128].…”
Section: Therapy Of Acute Hcv In Ckd Population (Dialysis Patients)mentioning
confidence: 99%